Analysis of Comparison of Islamic Banks with Online Micro In Disbursements of Micro-Financing Based on Requirements, Services Speed and Margin (Case Study of Micro-finance at Bank Mandiri Syariah and Micro Credit Uangteman.com) - Lucky Nugroho; Harnovinsah Harnovinsah; Yananto Mihadi Putra; Prinoti Prinoti (Universitas Mercu Buana, 2020)
The dynamics of the use of digital technology in the industrial revolution era 4.0 has had an impact on the financial sector. One of them is the development of financial technology (fintech) in the form of online loan services. Furthermore, the flagship product from fintech is lending to micro and small entrepreneurs. Likewise, Islamic banks that have a focus on financing to micro and small entrepreneurs must be able to compete with fintech services in the era of the industrial revolution 4.0 that is happening at this time. The purpose of this study is to analyze the different mechanisms of micro-financing distribution between Bank Mandiri Syariah and microcredit UangTeman.com. The method used is qualitative, which is to compare the requirements, mechanisms, and margins imposed on the customers and the information obtained through secondary data, namely standard and operational procedures. Based on the results of the study, the requirements and procedures for granting loans to micro and small entrepreneurs at Bank Mandiri Syariah are longer compared to UangTeman.com. While the fines for late payment in installments and interest rates on UangTeman.com are higher than the fines and margins of Bank Mandiri Syariah micro-financing. Therefore to be able to improve products and services for micro and small entrepreneurs, Bank Mandiri Syariah conducts a review of business models and business